Gestão integrada e sustentável da água em bacias hidrográficas: ferramentas, desafios e diretrizes - Cerezini, Monise Terra (2018)
The sustainability of development is an imperative issue in the discussions that permeate the problematic of the socioeconomic and environmental relationship in contemporary society. Actions to transmute the essence of this concept from theory to the practical issues applied to the management of natural resources are complex tasks, due to dynamic and interdisciplinary nature of the nature and society systems. This research was conducted under the theoretical concepts of integrated and sustainable management of water resources in river basin context and had as objective to identify the challenges for the effective water resources management and to understand if the existing tools are adequate to the management of water from the integrated and sustainable perspective. The purpose of this study was to analyze the main aspects necessary for the conservation and sustainable use of water resources, to investigate the use and applicability of the tools that support the decision-making process and to propose guidelines for integrated and sustainable water management. The main challenges related to the planning and management of water resources were identified through literature analysis and expert consultation using the Delphi technique. The tools were identified and analyzed based on a Global Water Partnership (GWP) ToolBox methodology that considers the principles of integrated water resources management. As a result, 60 tools currently used in various aspects of water resources management that address most aspects of Integrated Water Resources Management (IWRM) have been identified and can be used to support the decision-making process in water resources management. The main challenges identified in the water resources management refer to Knowledge and Education, Participation, Management Institution, Qualitative-Quantitative Balance, Management Tools, Financial Resources, Operational and Legal Articulation, Interest Conflicts, Data and Information and Human Resources. As result, an analysis was made of the tools applicability on the IWRM perspective and were defined guidelines to develop education and training practices, promote communication channels, dissemination and access to information, strengthen water resources management systems, value human resources, guarantee financial resources for the system, expand participatory management, implement management tools, decentralize water management and ensure the integrated water resources management.